2018
DOI: 10.3390/ijms19123866
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Comparative Proteomic Analysis Provides Insights into Molecular Mechanisms of Salt Tolerance in Sugar Beet (Beta vulgaris L.)

Abstract: Salinity is one of the major abiotic stress factors that limit plant growth and crop yield worldwide. To understand the molecular mechanisms and screen the key proteins in response of sugar beet (Beta vulgaris L.) to salt, in the present study, the proteomics of roots and shoots in three-week-old sugar beet plants exposed to 50 mM NaCl for 72 h was investigated by isobaric Tags for Relative and Absolute Quantitation (iTRAQ) technology. The results showed that 105 and 30 differentially expressed proteins (DEPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…In Yu et al [12] the changes were only induced by short-term salt stress (30 min and 1 h) and examined only proteome/phosphoproteome changes in M14 leaves. Finally, Wu et al studied proteome changes in seedlings, but only in shoots and roots, and after a very long exposure (50 mm NaCl for 72 h) [13]. While these studies are useful, we note that plant proteome responses to salt stress depend on its intensity, duration and the organ examined [14,15].…”
Section: Introductionmentioning
confidence: 89%
“…In Yu et al [12] the changes were only induced by short-term salt stress (30 min and 1 h) and examined only proteome/phosphoproteome changes in M14 leaves. Finally, Wu et al studied proteome changes in seedlings, but only in shoots and roots, and after a very long exposure (50 mm NaCl for 72 h) [13]. While these studies are useful, we note that plant proteome responses to salt stress depend on its intensity, duration and the organ examined [14,15].…”
Section: Introductionmentioning
confidence: 89%
“…Among environmental factors, salinity can have a serious impact on plant yield. With the reported rate of soil salinization 3 ha/min [1], salinity becomes a major challenge worldwide [2]. Moreover, the current trends in population dynamics, urbanization, and climate change will exacerbate the process of land salinization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this plant could be a good resource to explore salt tolerance mechanisms and to identify proteins and genes involved in salt tolerance [13]. Currently, proteomic studies on salt tolerance in sugar beet have been limited to tissues such as shoot, root, and leaf [2,14,15], with no studies on GCs reported to date. In this study, the GCs isolated for proteomic analysis were validated with microscopic observation, viability tests and comparing guard cell-specific proteins in mesophyll and guard cell samples.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al analyzed the changes in proteome and phosphoproteome of M14 leaves induced by short-term salt stress (30min and 1 hour) [12] . Wu et al studied changes in the proteome of beet seedlings treated with 50mm NaCl for 72h and 30 and 105 differentially expressed proteins were identified in the shoots and roots, respectively [13] . However, how plants respond to salinity depends on the organ, intensity and duration of the stress, which may lead to various changes at the proteome level [14,15] .…”
Section: Introductionmentioning
confidence: 99%